Major Cereal Crop Production in Kabhrepalanchok - Giri, Mira; Dahal, Dhundi Raj (Nepal Journal of Multidisciplinary Research, 2020)
Agriculture is one of the most vulnerable sectors to climate change impact. The main purpose of the study is to find the recent production of major cereal crops as rice, maize, and wheat per unit area in Banepa municipality, as a case study to the local trends and adaptation. The study was conducted among the household of ward No. 1, 3, 4, 5, 7, 8, 9, 10, and 11 in the Municipality. Field observation, in-depth interview, focus group discussion, Questionnaire survey methods were adopted for information collection, cross-validation with verification and using a secondary source of the information. Monthly precipitation and monthly minimum and maximum air temperatures data of Dhulikhel station were used to study their annual and seasonal trends. Time-series annual yield data in rice, maize, and wheat were collected from the Ministry of Agriculture and Livestock Development. Production was also accessed from the local level in a cross-sectional survey. Temperature and precipitation were collected from the Department of Hydrology and Metrology. The Survey indicated that yields have increased for major cereal crops and this led to an increase in the use of chemical fertilizer, chemical pesticides, improved seed, and improved management practices. The impacts of these changes have resulted in an increased attack of white grub in roots and maize smut in cobs, rice blast in panicle and stem, rust and blight disease and grain borer in wheat. The major issues for farmers were found to be a deficit of inorganic fertilizers, an insufficient supply of quality seeds and an unsystematic market. The coping mechanism for climate change in farming was not applied due to a lack of knowledge, facilities, and access to improved technologies. The farmers expected advanced technological know-how along with other facilities for climate-resilient farming. This study concludes that change in climate is affecting the agriculture in Banepa Municipality of Kabhrepalancchok. The existing local and institutional strategies are not sufficient and sustainable to cope with climatic vagaries. It is very important to address the problems in this region with institutional support and through a long-term policy perspective.